PERANCANGAN AUTOMATIC TEMPAT SAMPAH PADA SISTEM ARDUINO UNO R3 - Tanto wijaya Tanto; Agus Salim; Nur Nawaningtyas Pusparini (LPPM Universitas Putera Batam, 2023)
Automatic Design of Trash Cans in the Arduino Uno R3 System is designed for waste management which is often a problem in many cities. Waste management is currently one of the factors that always influences the creation of a clean and healthy environment. Garbage that is always left alone over time will accumulate and pile up so that no one takes care of it, irregular waste is a problem that often occurs. In the waste collection process, which will be carried out by checking the garbage collection sites one by one, the work will be ineffective and inefficient, because it will take a lot of wasted time, even time and money. Furthermore, to simplify the waste disposal process, this can be done at any time, because the process is very easy and can be done or done by anyone. The result is that the ultrasonic sensor is used to capture objects or objects in front of it, then there is a servo motor that can move when someone throws trash, after that there is an LCD display that will display an inscription, after that there is also a mini speaker that makes a sound if someone has finished taking out the trash. So the conclusions that can be studied in this study are how to design an Automatic Trash Can on the Arduino Uno R3 System which can open the lid of the trash can by itself.